Secret schools in Lithuania in the second half of the 20th century - Vėbra, R. (Psichologija, 1968)
The fight for national schools together with the struggle for the Lithuanian press and the national church constitutes one of the most prominent Lithuanian national movements in history. So far, no work has analyzed in more detail the Czarist government’s position with respect to private education in Lithuania or the impetus of the secret schools. This article is written based on new archival data found in the USSR in the Central State Historical Archive in Leningrad. Even in the first half of the nineteenth century Lithuania’s private education system was well developed. During the first half of the sixties, with the intensification of the reaction, the tsarist government administration conducted a rigorous centralization of the education system. Laws were adopted prohibiting private training establishments, and Russian language teaching was introduced in the remaining schools. The Czarist regime termed private teaching of group "secret schools" and fought with them until the abolition of martial law in 1872. With the withdrawal of martial law the military administration officials maintained only the right to bring actions before the judicial authorities for court proceedings. The courts did not consider these cases political proceeding and in many cases a fine of from only 0.25 to 2 rubles was handed down, or they were even found not guilty. This article contains a table showing how the czarist administration officials found secret schools in 1872-1882 in the rural districts of Kaunas Governorate and Vilnius Governorate. Of the 126 schools in Kaunas Governorate only 25 were fined; for Vilnius it was 63 out of 225. Every year the number of secret schools grew. Czarist officials were not pleased. Active correspondence took place regarding this question starting in 1887 between the northwest administration of the Russian Empire and the central institutions. The result of the northwest administration’s demands was that a decision was made on April 2, 1892, to establish Provisional Regulations forbidding private teaching and establishing penalties. Suwalki Governorate was in a better position compared with Kaunas and Vilnius, because here the Provisional Regulations of April 2, 1892, only entered into force on 26 May 1900. This article spends time explaining private group teaching and showing that secret schools were opened for a variety of reasons. Secret schools were not only Lithuanian, but also Polish, Jewish, and even Russian. Persecution of the secret schools was unsuccessful. Census data from 1897 shows that Lithuanians used to acquire basic literacy specifically in secret schools.